2008
DOI: 10.1007/s00404-008-0867-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of molecular classification of breast invasive ductal carcinoma

Abstract: Molecular classification with immunohistochemistry behaves as a significant prognosticator for breast invasive ductal carcinoma in our series of patients. The worse prognosis observed for Her2 expressing lesions may have changed after trastuzumab use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The median durations of survival with distant metastasis of HER-2 enriched type and TNBC was only 0.7 and 0.5 years respectively, compared with the luminal type which was from 1.3 to 1.6 years. Munoz et al also concluded that patients with HER-2 enriched tumors or TNBC had a worse outcome with the higher recurrence and mortality rate, shorter relapse free survival and overall survival [25]. Nonetheless, the mechanisms underlying the aggressive behaviors of BC subtypes and prognosis are still unclear.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The median durations of survival with distant metastasis of HER-2 enriched type and TNBC was only 0.7 and 0.5 years respectively, compared with the luminal type which was from 1.3 to 1.6 years. Munoz et al also concluded that patients with HER-2 enriched tumors or TNBC had a worse outcome with the higher recurrence and mortality rate, shorter relapse free survival and overall survival [25]. Nonetheless, the mechanisms underlying the aggressive behaviors of BC subtypes and prognosis are still unclear.…”
Section: Discussionmentioning
confidence: 96%
“…In our meta-analysis, EZH2 was also found to be associated with the race of BC patients, which implied that EZH2 expression was higher in other racial women than that in white women. Primary molecular subtypes of breast tumors have been defined by clinical markers: Luminal tumors (ER/PR positive and HER-2 negative), HER-2 enriched tumors (ER/PR negative and HER-2 positive) and TNBC (with all markers negative) [25]. Biological behaviors and prognoses of BC with different molecular phenotypes are different [26].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have replicated the finding that basal-like breast cancer is more common in young African Americans [3, 9,10] and younger women in Africa [11, 12] compared to European American, European, and Asian women [3-8, 1321]. Additionally, nearly all studies agree that basal-like and HER2+/ER- negative tumors have poorer prognoses than luminal A, regardless of the source population [3, 4, 6, 7, 10, 1524].…”
Section: Introductionmentioning
confidence: 83%
“…With the advances in molecular biological research, a more in-depth understanding of breast cancer has been developed. Nowadays, breast cancer can be generally classified into luminal A, luminal B, human epidermal growth factor receptor 2 (HER2)-enriched, and triple negative breast cancer (TNBC) based on the presence or absence of the estrogen receptor (ER), progesterone receptor (PR), HER2, and Ki-67 (Ihemelandu et al, 2007;Muñoz et al, 2009;Wiechmann et al, 2009;Park et al, 2012). Breast cancer is a heterogeneous disease consisting of different molecular subtypes with different molecular biological characteristics and clinical behaviors.…”
Section: Introductionmentioning
confidence: 99%